Evolución del concepto de cambio climático y su impacto en la salud pública del Perú - Sánchez Zavaleta, Carlos A. (2016)
The term “climate change” is not a new concept but its impact on public health is under constant review. We know that climate has already changed and will continue to change for centuries with the rise in average global temperature, and the associated rise in sea level. This fact makes mitigation efforts relevant only in the very long term and for generations of humans whose parents have not yet been born. When we talk about public health in the context of climate change, we are talking about adaptation. In the present, countries that are currently the most affected by climate change are precisely countries like Peru, without a significant carbon footprint at the global level but that are highly sensitive to the effects of climate. Without reliable climate projections, the health impact of climate change can be uncertain and complicated. Nevertheless, at the local level, every district can identify its vulnerabilities and define priorities to protect the health of its population. There are, and it can also be developed, environmental health indicators that can help monitor how well we are adapting and how prepared we are for changes in the climate. Adaptation to climate change implies improving living conditions, enhancing epidemiological surveillance systems and extending access to healthcare. The fight against the effects of climate change in public health is a fight against poverty and inequality, and that is nothing new in Peru.